1993
DOI: 10.2166/wst.1993.0073
|View full text |Cite
|
Sign up to set email alerts
|

Feed Characteristics and Digester Operative Conditions as Parameters Affecting the Rheology of Digested Municipal Solid Wastes

Abstract: The rheology of pre-composted and fresh organic fractions of municipal solid wastes (OFMSW) anaerobically digested in thermophilic range of temperature and different operative conditions is presented. Rheological properties are strongly influenced by feed characteristics and the biodEgradation achieved. The metabolization of complex substrates has been invoked to explain different behaviours. A semiempirical model of plastic viscosity with total volatile solids, organic loading rate removed and specific gas pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…This would be expected, since an increase in TS often results in a higher fluid viscosity (Seyssiecq et al 2003). This is in agreement with Battistoni et al (1993;Battistoni 1997), who reported that the rheological characteristics of OFMSW specifically were correlated with the total TS and VS. The viscosity of the reactor sludge in the control reactor (R2) ranged between 2.0 ± 0.2 and 7.7 ± 0.3 mPa*s throughout the experiment (Fig.…”
Section: Resultssupporting
confidence: 89%
“…This would be expected, since an increase in TS often results in a higher fluid viscosity (Seyssiecq et al 2003). This is in agreement with Battistoni et al (1993;Battistoni 1997), who reported that the rheological characteristics of OFMSW specifically were correlated with the total TS and VS. The viscosity of the reactor sludge in the control reactor (R2) ranged between 2.0 ± 0.2 and 7.7 ± 0.3 mPa*s throughout the experiment (Fig.…”
Section: Resultssupporting
confidence: 89%
“…These results are consistent with the literature (Battistoni et al, 1993;Battistoni, 1997;Baudez, 2008;Baudez et al, 2011) and close to those obtained by Garcia-Bernet et al (2011). The slight differences observed between all those results may be explained either by the type of digested wastes considered in each paper or by the fact that we consider the apparent viscosity instead of the yield stress.…”
Section: Resultssupporting
confidence: 92%
“…No comparative analysis of rheology was found for digested wastes from different origins, solid concentration as well as particles interactions. In this paper, we compared different types of anaerobically digested wastes and we demonstrated that regardless of their origin, their rheological behaviour is mainly driven by both the total solids and the total volatile solids, as stated by Garcia-Bernet et al (2011) but also by Battistoni (1997) and Battistoni et al (1993).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To explain the different behaviors, the relationship between rheological parameters and sludge composition has been examined and in all the cases, the total solid content appeared to be the main factor governing the behavior (Battistoni, 1997;Battistoni et al, 1993Battistoni et al, , 2000Slatter, 1997). Nevertheless, according to Lotito et al (1997), a single factor did not appear sufficient to explain the variations of at least two independent parameters (yield stress, consistency index (and power-law index)).…”
Section: Introductionmentioning
confidence: 99%